Intervention decision‐making processes and information preferences of parents of children with autism spectrum disorders. (22nd October 2015) - Grant, N.; Rodger, S.; Hoffmann, T.
Abstract: Background: When a child is diagnosed with autism, parents are faced with the task of choosing from many different intervention options. To find information about the options available, parents turn to a number of different sources. This study explores parents' ( n = 23) intervention decision‐making processes and information preferences following the diagnosis of ASD for their child. Methods: Qualitative thematic analysis of verbatim transcripts from interviews and focus groups involving parents of children with an autism diagnosis was undertaken. Results: Analysis of the results revealed that there are concurrent emotional and pragmatic intervention 'journeys' undertaken by parents post diagnosis, which encompass the primary themes of: (1) information sources used, (2) parents' information preferences and (3) factors influencing intervention decision making. Parents described a journey from the point of diagnosis that involved seeking information on ASD interventions from multiple sources, with the Internet being the primary source. They were overwhelmed by the sheer volume of information available, and their preferences for information varied according to their stage in the journey post diagnosis. Parents had a 'trial and error' approach to choosing ASD interventions, with confidence increasing as they became more familiar with their child's condition, and had opportunities to explore numerous information sources about their child's diagnosis. While confidence increased over time, consideration of the effectiveness or evidence supporting interventions remained largely absent throughout the journey. Conclusion: This study highlights the need for parents of children with ASD to be supported to make informed intervention decisions, particularly with consideration for research evidence.